2011
DOI: 10.1111/j.1834-7819.2011.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandible fracture severity may be increased by alcohol and interpersonal violence

Abstract: Background: Alcohol as a cofactor in interpersonal violence (IPV) has been established by studies from a number of countries. This study aimed to determine if alcohol was a cofactor in the incidence or severity of mandible fracture. Methods: A prospective study of mandible fracture patients presenting for oral maxillofacial review over 16 months was completed. Injury severity was assessed utilizing the Mandible Injury Severity Score (MISS). Results: A total of 252 facial trauma cases presented to our tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
3
15
0
2
Order By: Relevance
“…This finding is consistent with reports by Obuekwe ON et al 23 Studies published by Lee KH et al 27 , Snape L et al 28 and O Meara C et al 29 have also found the interpersonal violence to be a major cause of maxillofacial trauma when alcohol is involved. However, in our study RTA was the major cause of maxillofacial trauma.…”
Section: Resultssupporting
confidence: 83%
“…This finding is consistent with reports by Obuekwe ON et al 23 Studies published by Lee KH et al 27 , Snape L et al 28 and O Meara C et al 29 have also found the interpersonal violence to be a major cause of maxillofacial trauma when alcohol is involved. However, in our study RTA was the major cause of maxillofacial trauma.…”
Section: Resultssupporting
confidence: 83%
“…(Table 6) Another report also concluded that 17.8%-41.4% of fracture cases were related to alcohol1,5,8,10. The degree of injury was more severe when an individual was injured under the influence of alcohol11,12.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the city of Diamantina is the center pole of the Jequitinhonha Expanded Health Region, being then reference for 24 cities, it is verified that it is fulfilling well its role in the regionalization of health. The percentage of treatment for multiple facial fractures was higher than the other procedures (54.7%), even than the single mandible fractures that are mentioned by some authors as the most prevalent [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The treatment of simple facial fractures was reported by Montovani et al [6] in 72.3% of the cases in a study conducted in the interior of the state of São Paulo.…”
Section: Discussionmentioning
confidence: 99%
“…Motorcycle accidents as cause of facial trauma were also the most prevalent in the study by Silva et al [11], being responsible for 44% of all cases. However, the literature has reported a gradual change in the etiology of facial fractures, with interpersonal violence overcoming the vehicles accident as the most common cause [3][4][5][6][7][8][9][10][11][12][13][14][15]. Although in recent years many traffic policies have been instituted aiming a greater safety in public roads [16], many laws, such as the compulsory use of helmets and driver's licenses, are not respected in small towns that prevail in the Jequitinhonha valley.…”
Section: Discussionmentioning
confidence: 99%